2010
DOI: 10.4271/2010-01-1457
|View full text |Cite
|
Sign up to set email alerts
|

A Turbulent Jet Ignition Pre-Chamber Combustion System for Large Fuel Economy Improvements in a Modern Vehicle Powertrain

Abstract: Turbulent Jet Ignition is an advanced pre-chamber initiated combustion system for an otherwise standard spark ignition engine found in current on-road vehicles. This next generation pre-chamber design overcomes previous packaging obstacles by simply replacing the spark plug in a modern four valve, pent roof spark ignition engine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(83 citation statements)
references
References 45 publications
0
83
0
Order By: Relevance
“…Previous studies [14,15,16,17] have demonstrated the potential of TJI as an enabling technology for ultra-lean SI combustion to significantly increase thermal efficiency and reduce NO x emissions. This study seeks better understanding of TJI combustion, specifically in terms of main chamber ignition and the dynamics of the interaction between the pre-chamber and main chamber.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [14,15,16,17] have demonstrated the potential of TJI as an enabling technology for ultra-lean SI combustion to significantly increase thermal efficiency and reduce NO x emissions. This study seeks better understanding of TJI combustion, specifically in terms of main chamber ignition and the dynamics of the interaction between the pre-chamber and main chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-chamber combustion concepts have demonstrated the potential for stable main chamber combustion at higher levels of dilution than are allowable in typical SI engines [14]. They have also demonstrated the ability to counter the loss of ignitability of the lean charge to a certain extent.…”
Section: Methodology For Combustion Analysis Of a Spark Ignition Engimentioning
confidence: 98%
See 1 more Smart Citation
“…The flame jets issued from pre-chamber create multiple ignition sites leading to rapid combustion in the main chamber. A more feasible jet ignition system named Turbulent Jet Ignition (TJI) was developed by MAHLE Powertrain [20,21]. The fuel consumption was reduced by nearly 25% at part load.…”
Section: Introductionmentioning
confidence: 99%
“…About the same power and fuel efficiency may also be delivered with stoichiometric engines direct injection jet ignition two-stroke of 750 cm 3 .Application to premixed mixtures has been fostered by ex-students of Prof. H.C. Watson, then working in Mahle and the University of Michigan since 2009. Developments by Mahle are reported in the use of jet ignition with premixed more than stratified mixtures [10][11][12][13][14][15][16].Application to lean stratified mixtures by jet ignition has been mostly nurtured by the author, who was a collaborator of Prof. H.C. Watson from 2006 to 2009, working largely unsupported as independent scientist.Jet ignition was proposed as a coupling to direct injection to work lean stratified, [17][18][19][20][21]. The advantage of the coupling was the opportunity to produce a central cloud of nearly stoichiometric mixture at the center of the combustion chamber with a surrounding cushion of air then bulk, high energy, ignited by multiple jets of hot reacting gases and rapidly and completely burned with reduced heat losses.…”
mentioning
confidence: 99%